Community Structure of Dragonfly (Anisoptera) and Damselfy (Zygoptera) at The Gunung Sigogor Nature Reserve, East Java, Indonesia - Susanto, Muhamad Azmi Dwi; Priambodo, Bagus; Firmansyah, Richo; Pranata, Dicky Candra; Aninnas, Afina Nur; Aji, Fajar Dwi Nur; Widodo, Tri Wahyu; Gunawan, Gunawan; Permana, Danafia; Adiba, Faisal Yanuar; Ristanto, Yuri; Erfanda, Muhamad Prayogi; Kadafi, Ahmad Muammar (Universitas Islam Negeri Mataram, 2021)
Gunung Sigogor Nature Reserve is a conservation forest administratively located in Ngebel District, Ponorogo Regency, East Java, Indonesia. The dragonfly and damselfly community structure, which includes diversity, abundance, evenness and dominance, can be used as an early indicator of changes in environmental conditions, especially in aquatic ecosystems. This study aimed to determine dragonfly and damselfly’s community structure, diversity, evenness, dominance, and habitat preference. This study uses the Visual Encounter Survey (VES) observation and transect methods. This method is carried out by tracing all predetermined observation stations by recording the diversity of dragonfly species and counting the number of individuals. The study conducted in the Gunung Sigogor Nature Reserve area showed 15 species from 8 families consisting of 9 species of Suborder Anisoptera and six species of Suborder Zygoptera. In the results, the highest diversity index value was in the Small Stream (S3) with H'= 1.84. The evenness index, Goa Jepang Stream (S5), has the highest value with a value of E=0.9, and the dominance index of Watu Bandar Stream (S6) location has the highest value with a value of C=1.